Development of tissue scaffold for bone tissue engineering using rapid prototyping technique - Too, Mui Heng. (2008)
Tissue Engineering (TE) merges the fields of cell biology, engineering, material science and surgery to fabricate new functional tissue using living cells and a matrix or scaffolding method. It involves the development of methods to build biological substitutes as supplements to whole organ or tissue transplantation.